2009
DOI: 10.2175/106143009x407285
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Nitration Kinetics and Implications for Wastewater Treatment

Abstract: Understanding estrogen‐removal mechanisms in wastewater treatment is imperative, as estrogens have environmental effects at trace concentrations. Previous research investigating co‐metabolic degradation of 17α‐ethinylestradiol (EE2) by ammonia‐oxidizing bacteria (AOB) revealed that, in batch tests where high nitrite‐nitrogen (NO2‐N) concentrations occurred as a result of ammonia‐nitrogen (NH4‐N) oxidation by AOB, an abiotic estrogen nitration reaction actually was occurring—not co‐metabolic degradation. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The formation of nitrated products was shown in pure and mixed nitrifying cultures for the estrogen 17α-ethinyl estradiol (EE2) and acetaminophen, being associated with significant accumulation of nitrite or peroxynitrite and acidic pH conditions. Nitrated and nitrosated derivatives were further identified and quantified (at low ng L –1 levels) in full-scale WWTPs for SMX and diclofenac. Although nitration and nitrosation appear of limited importance during conventional treatment of domestic wastewater, these mechanisms may be relevant to the treatment of high strength reject water and/or in deammonification and nitrite shunt processes, where nitrite accumulation is more likely to occur. Notably, parent SMX was shown to be abiotically formed from its nitrosated (via photolysis) and nitrated derivatives.…”
Section: Factors and Processes Influencing Antibiotic Removal In Wwtpsmentioning
confidence: 99%
“…The formation of nitrated products was shown in pure and mixed nitrifying cultures for the estrogen 17α-ethinyl estradiol (EE2) and acetaminophen, being associated with significant accumulation of nitrite or peroxynitrite and acidic pH conditions. Nitrated and nitrosated derivatives were further identified and quantified (at low ng L –1 levels) in full-scale WWTPs for SMX and diclofenac. Although nitration and nitrosation appear of limited importance during conventional treatment of domestic wastewater, these mechanisms may be relevant to the treatment of high strength reject water and/or in deammonification and nitrite shunt processes, where nitrite accumulation is more likely to occur. Notably, parent SMX was shown to be abiotically formed from its nitrosated (via photolysis) and nitrated derivatives.…”
Section: Factors and Processes Influencing Antibiotic Removal In Wwtpsmentioning
confidence: 99%
“…Of greater interest may be abiotic transformation of steroids due to redox conditions within the benthic environment caused by the accumulation of organic matter, nutrients, and other reductants. While little information is available regarding the effects of abiotic processes on 17β-Tb fate, estrogens have been shown to undergo catylitic conversion (Vega et al, 2010) and nitration (Gaulke et al, 2009) in the presence of organic matter and nitrites, as well as, oxidation when exposed to soils containing manganese oxides (Sheng et al, 2009). …”
Section: β-Trenbolone Fate and Bioavailability In Aquatic Systemsmentioning
confidence: 99%
“…Nitration of phenols proceeds via a number of different mechanisms involving both biotic and abiotic processes. Gaulke et al proposed that abiotic nitration of estrogens in wastewater treatment plants (WWTP) is mediated by nitrous acid, in dependency of its concentration, pH, and temperature . Also Jewell et al found that nitration of bisphenol A (BPA), dextrophan, and OPP is caused by the formation of radicals from nitrous acid, however, only at low pH and elevated nitrite concentrations .…”
Section: Resultsmentioning
confidence: 99%